Ulinastatin Reduces Cancer Recurrence after Resection of Hepatic Metastases from Colon Cancer by Inhibiting MMP-9 Activation via the Antifibrinolytic Pathway - Jia, Lin; Li, Jiang-lin; Cai, Wen-song; Xiao, Huan-qing; Shen, Fei; Li, Kun-ping; Xu, Bo; Liu, Qi-cai (BioMed research international, 2013)
High recurrence of colon cancer liver metastasis is observed in patients after hepatic surgery, and the cause is believed to be mostly due to the growth of residual microscopic metastatic lesions within the residual liver. Therefore, triggering the progression of occult metastatic foci may be a novel strategy for improving survival from colon cancer liver metastases. In the present study, we identified an anti-recurrence effect of ulinastatin on colon cancer liver metastasis in mice after hepatectomy. Transwell cell invasion assays demonstrated that ulinastatin significantly inhibited the in vitro invasive ability of colon cancer HCT116 cells. Moreover, gelatin zymography and ELISA analysis showed that MMP-9 activity and plasmin activity of colon cancer HCT116 cells were inhibited by ulinastatin, respectively. Furthermore, in vivo BALB/C nu/nu mice model indicated that ulinastatin effectively reduced recurrence after resection of hepatic metastases from colon cancer. The optimum timing for ulinastatin administration was one week after hepatectomy. Taken together, our findings point to the potential of ulinastatin as an effective approach in controlling recurrence of hepatic metastases from colon cancer after hepatectomy via its anti-plasmin activity.